2021
DOI: 10.1161/jaha.120.021560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Religious Fasting in Ramadan on Blood Pressure: Results From LORANS (London Ramadan Study) and a Meta‐Analysis

Abstract: Background Ramadan fasting is practiced by hundreds of millions every year. This ritual practice changes diet and lifestyle dramatically; thus, the effect of Ramadan fasting on blood pressure must be determined. Methods and Results LORANS (London Ramadan Study) is an observational study, systematic review, and meta‐analysis. In LORANS, we measured systolic blood pressure (SBP) and diastolic blood pressure (DBP) of 85 participants before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 54 publications
1
20
1
2
Order By: Relevance
“…The LORANS (London Ramadan Study) is an observational, systematic review, and meta-analysis. 18 In LORANS, the systolic blood pressure (SBP) and diastolic blood pressure (DBP) of 85 participants were measured before and right after Ramadan. In the systematic review, studies were retrieved from several databases.…”
Section: Highlights Of the Year's Literaturementioning
confidence: 99%
“…The LORANS (London Ramadan Study) is an observational, systematic review, and meta-analysis. 18 In LORANS, the systolic blood pressure (SBP) and diastolic blood pressure (DBP) of 85 participants were measured before and right after Ramadan. In the systematic review, studies were retrieved from several databases.…”
Section: Highlights Of the Year's Literaturementioning
confidence: 99%
“…Of the 27 included reviews, only one systematic review ( 21 ) and a scoping review ( 22 ) evaluated the effects of Orthodox fasting on health/nutritional outcomes. The remainder reviews ( n = 25) focused on the effects of Ramadan fasting on anthropometric and metabolic markers ( 23 25 ), glucometabolic parameters ( 26 29 ), salivary flow rate, inflammatory and metabolic variables ( 30 ), immunity, inflammatory markers and infectious events ( 31 33 ), blood pressure and cardiovascular events ( 34 36 ), liver function ( 37 ), renal function and chronic kidney diseases ( 38 , 39 ), body mass (i.e., body weight) and body composition ( 40 42 ), intestinal microbiome changes ( 43 ), hormones regulating appetite and satiety ( 44 ), psychiatric parameters ( 45 ), sleep quality ( 46 ) and pregnancy outcomes ( 47 ). The characteristics and the main outcomes of the included reviews are presented in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded Ramadan fasting positively impacts cardiometabolic risk factors, which may provide healthy persons short-term protection against cardiovascular diseases ( 29 ). The beneficial effect of Ramadan fasting on systolic and diastolic blood pressure was originally proposed in the meta-analysis by Al-Jafar et al ( 36 ).…”
Section: Religious Fasting Nutrition and Individual Healthmentioning
confidence: 99%
“…In this meta-analysis and observational study subgrouping of pooled data showed SBP and DBP reduction among healthy, hypertensive and diabetic subgroups but not in the CKD subgroup. 23 Many factors may theoretically influence the blood pressure (BP) during Ramadan. These include feeding patterns, sleep changes and changes in the timing of intake of medication.…”
Section: % 61%mentioning
confidence: 99%